Women and the Gift : Beyond the Given and All-Giving - Joy, Morny (Book collections on Project MUSE., 2013)
Recent inquiries into the concept of the gift have been largely male-dominated and thus have ignored important aspects of the gift from a woman's point of view. In the light of philosophical work by Mauss, Levi-Strauss, Derrida, and Bataille, this book reflects how women respond to the notion of the gift and relationships of giving. This collection evaluates and critiques previous work on the gift and also responds to how women view care, fidelity, generosity, trust, and independence in light of the gift.